Comparative Assessment of Rework on Buildings in Akure Municipal, Ondo State, Nigeria - Abiodun, Oluwapelumi; Nwaogu, Janet (International Journal of Sustainable Construction Engineering and Technology, 2021)
Rework is the repetition of work that constitutes waste in construction and reflects poor performance due to the failure of building components to satisfy client’s requirement and contract documentation’s provision which further results in cost and time overrun. In lieu of the nature of the subject matter, this study comparatively assessed rework occurrence on buildings in Akure municipal, Ondo state, Nigeria to ensure the building works prone to rework are carried out with utmost care and control to drastically reduce rework cost. A total of eighty-three (83) well-structured closed-ended questionnaires were distributed and the retrieved seventy (70) questionnaires formed 84% response rate. Primary data were obtained from 10 construction firms and 60 end-user clients using purposive and snowball sampling. Data collected from the retrieved questionnaires were on the defects in building components due to non-conformance to specification and client requirement and perception on the frequency of occurrence and cost of rework on buildings. The data were analysed using frequency, percentage, Relative Importance Index (RII), Mean Item Score, Mann-Whitney U Test and Spearman’s Rank Correlation Coefficient. A descriptive analysis of the defects on building components from the end-user clients and construction professionals revealed Plumbing and sanitary system and electrical services as the most defective respectively. Further analysis on the parameters shows no significant relationship between the opinions of the end-user clients and professionals on the defects in the electrical appliances and installation; corrosion and discolouration of components; doors and accessories and ceiling and accessories. However, a significant relationship exists between the overall opinions of the end-user clients and the construction professionals on building component defects. The result of the conducted analysis further showed that an increase in the frequency of occurrence of rework on finishes and mechanical installations could speed up rework cost. The study concluded that stakeholders need to avoid rework occurrence on services components (mechanical and electrical), concrete works and finishes in order to experience a rapid decline in the cost of rework.